New Perspective for Non-invasive Brain Stimulation Site Selection in Mild Cognitive Impairment: Based on Meta- and Functional Connectivity Analyses - Liu, Jiao; Zhang, Binlong; Wilson, Georgia; Kong, Jian; , the Alzheimer’s Disease Neuroimaging Initiative; Weiner, Michael W.; Aisen, Paul; Weiner, Michael; Aisen, Paul; Petersen, Ronald; Jack, Clifford R.; Jagust, William; et al. (Frontiers in Aging Neuroscience, 2019)
Background: Non-invasive brain stimulation (NIBS) has been widely used to treat mild cognitive impairment (MCI). However, there exists no consensus on the best stimulation sites. Objective: To explore potential stimulation locations for NIBS treatment in patients with MCI, combining meta- and resting state functional connectivity (rsFC) analyses. Methods: The meta-analysis was conducted to identify brain regions associated with MCI. Regions of interest (ROIs) were extracted based on this meta-analysis. The rsFC analysis was applied to 45 MCI patients to determine brain surface regions that are functionally connected with the above ROIs. Results: We found that the dorsolateral prefrontal cortex (DLPFC) and inferior frontal gyrus were the overlapping brain regions between our results and those of previous studies. In addition, we recommend that the temporoparietal junction (including the angular gyrus), which was found in both the meta- and rsFC analysis, should be considered in NIBS treatment of MCI. Furthermore, the bilateral orbital prefrontal gyrus, inferior temporal gyrus, medial superior frontal gyrus, and right inferior occipital gyrus may be potential brain stimulation sites for NIBS treatment of MCI. Conclusion: Our results provide several potential sites for NIBS, such as the DLFPC and inferior frontal gyrus, and may shed light on the locations of NIBS sites in the treatment of patients with MCI.